Subtle changes in Purkinje cell firing in Purkinje cell-specific Dyt1 ΔGAG knock-in mice - Hong Xing; Pallavi Girdhar; Yuning Liu; Fumiaki Yokoi; David E. Vaillancourt; Yuqing Li (Dystonia)
DYT1 dystonia is an inherited early-onset generalized dystonia characterized by sustained muscle contractions causing abnormal, repetitive movements or postures. Most DYT1 patients have a heterozygous trinucleotide GAG deletion (ΔGAG) in DYT1/TOR1A, coding for torsinA. Dyt1 heterozygous ΔGAG knock-in (KI) mice or global KI mice show motor deficits and abnormal Purkinje cell firing. However, Purkinje cell-specific heterozygous ΔGAG conditional KI mice (Pcp2-KI) show improved motor performance, reduced sensory-evoked brain activation in the striatum and midbrain, and reduced functional connectivity of the striatum with the anterior medulla. Whether Pcp2-KI mice show similar abnormal Purkinje cell firing as the global KI mice, suggesting a cell-autonomous effect causes the abnormal Purkinje cell firing in the global KI mice, is unknown. We used acute cerebellar slice recording in Pcp2-KI mice to address this issue. The Pcp2-KI mice exhibited no changes in spontaneous firing and intrinsic excitability compared to the control mice. While membrane properties were largely unchanged, the resting membrane potential was slightly hyperpolarized, which was associated with decreased baseline excitability. Our results suggest that the abnormal Purkinje cell firing in the global KI mice was not cell-autonomous and was caused by physiological changes elsewhere in the brain circuits. Our results also contribute to the ongoing research of how basal ganglia and cerebellum interact to influence motor control in normal states and movement disorders.